Domitian at the Contra-Temple of Karnak - Klotz, David (Zeitschrift für ägyptische Sprache und Altertumskunde, 2008)
A new translation of the Roman Period inscriptions on the Eighteenth Dynasty contra-temple of Karnak, attached to the rear of the Akh-Menu. These religious texts lead to a reconsideration of the cultic function of this and other contra-temples, previously considered exclusively as locations for popular worship. The inscriptions from the reign of Domitian are primarily solar, associating the contra-temple with the nearby horned altar, sole obelisk, and East temple of Ramesses II, in the section of Karnak called ′the Benben temple.′ The form of Amun in this section was simultaneously ,Amun who hears prayers′ and the newly reborn sundisk who massacres his enemies in the Eastern horizon. The dual role of Amun as healer and punisher (i. e. ,Good Ka, Bad Ka′) combines Heliopolitan theology with the traditional role of gates as places for administering justice, appropriate for the one location where Amun of Karnak could approach the masses, both the faithful and the wicked.